God's wrath and judgment on ethnic hatred and hope for victims of ethnic hatred in Obadiah : implications for Africa - Adu-Gyamfi, Yaw (Old Testament essays, 2015)
Ethnic hatred has caused many lives on the African continent. In many cases victims of ethnic hatred are left without hope for the future. The book of Obadiah shows that there is hope for victims of ethnic hatred. This article looks at the book from the viewpoint that considers God's wrath and judgment on ethnic hatred, his assurance of justice and his plan to give hope to victims of ethnic hatred. Compared to Judah's misfortune, the Edomites used their advantage to participate in the destruction of "a brother" nation. But God would administer justice which would lead to the abasement of Edom and offer hope to Judah. Victims of ethnic hatred in Africa should console themselves with the fact that God will administer justice that would see to the punishment of those who take advantage of their condition and offer them (victims of ethnic hatred) a better future.